How do you simplify #(2hj^2k^-2*h^4j^-1k^4)^0/(2h^-3j^-4k^-2)# and write it using only positive exponents?

1 Answer
Aug 24, 2017

Answer:

See a solution process below:

Explanation:

First, we can simplify the numerator using this rule of exponents"

#a^color(red)(0) = 1#

#(2hj^2k^-2*h^4j^-1k^4)^color(red)(0)/(2h^-3j^-4k^-2) => #

#1/(2h^-3j^-4k^-2)#

Now, we can use this rule for exponents to eliminate the negative exponents:

#1/x^color(red)(a) = x^color(red)(-a)#

#1/(2h^color(red)(-3)j^color(red)(-4)k^color(red)(-2)) =>#

#(h^color(red)(- -3)j^color(red)(- -4)k^color(red)(- -2))/2 =>#

#(h^color(red)(3)j^color(red)(4)k^color(red)(2))/2#